2002
DOI: 10.1093/nar/30.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric inhibitors of telomerase: oligonucleotide N3'->P5' phosphoramidates

Abstract: Telomerase is a ribonucleoprotein responsible for maintaining telomeres in nearly all eukaryotic cells. The enzyme is able to utilize a short segment of its RNA subunit as the template for the reverse transcription of d(TTAGGG) repeats onto the ends of human chromosomes. Transfection with telomerase was shown to confer immortality on several types of human cells. Moreover, telomerase activation appears to be one of the key events required for malignant transformation of normal cells. Inhibition of telomerase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Interestingly, we found that several sequenceextended versions of cluster IV RIPtides showed nanomolar IC 50 values in TRAP assays (supplemental Table 1, entries [35][36][37][38][39][40]. These observations are consistent with previous observations that longer DNA oligonucleotides targeting an overlapping region in hTR exhibit inhibitory activity against telomerase in vitro (45).…”
Section: -Ome Riptide Microarrays and Telomerase Inhibitionsupporting
confidence: 88%
“…Interestingly, we found that several sequenceextended versions of cluster IV RIPtides showed nanomolar IC 50 values in TRAP assays (supplemental Table 1, entries [35][36][37][38][39][40]. These observations are consistent with previous observations that longer DNA oligonucleotides targeting an overlapping region in hTR exhibit inhibitory activity against telomerase in vitro (45).…”
Section: -Ome Riptide Microarrays and Telomerase Inhibitionsupporting
confidence: 88%
“…38 The hTR contains a crucial 11-nucleotide-long template region, part of which serves as the basis for telomere elongation by TTAGGG repeats. GRN163 forms a high-affinity sequence-specific duplex with the complementary RNA strand that is further stabilized through interactions between the oligonucleotide backbone and hTERT.…”
Section: Resultsmentioning
confidence: 99%
“…GRN163 is a prototype of a new class of 13-mer 2Ј-deoxy N3Ј3P5Ј thiophosphoramidate oligonucleotides designed to complement the template domain of the RNA component (hTR) in the active site of telomerase. 38 The GRN163 compound forms a high-affinity, sequence-specific duplex with the complementary RNA strand that is further stabilized through interactions between the oligonucleotide backbone and hTERT, is resistant to hydrolysis by cellular nucleases, and exhibits high thermodynamic stability. 30 The effects of GRN163 were evaluated on the growth of human MM and NHL cell lines, primary MM cells, and tumor xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…NP oligonucleotides were targeted at a segment of hTR downstream from the hTR template region, but (Pruzan et al 2002). The same group then tested the anti-telomerase effect of N3 0 !P5 0 thio-phosphoramidate oligonucleotides (NPS).…”
Section: N3mentioning
confidence: 99%